Complete testicular feminization caused by an amino-terminal truncation of the androgen receptor with downstream initiation. - Zoppi, S (1993)
We have characterized the molecular defect causing androgen resistance in two 46,XY siblings with complete testicular feminization. Although binding studies in genital skin fibroblasts showed a reduced Bmax, an increased dissociation rate of ligand, and an 8S peak of dihydrotestosterone binding on sucrose density gradient centrifugation, no immunoreactive androgen receptor (AR) was detected in immunoblots using anti-NH2-terminal antibodies, suggesting an abnormal amino terminus. Sequence analysis of the AR gene revealed a point mutation CAG-->TAG (Gln-->Stop) at nucleotide 340. In vitro mutagenesis studies suggest the synthesis of the mutant AR is initiated downstream of the termination codon at reduced levels and that each molecule is functionally impaired. These results define a novel mechanism causing androgen resistance: the combination of decreased amount and functional impairment of AR caused by an abnormality within the amino terminus of the receptor. These findings suggest that domains important to the in vivo function of the receptor reside within the amino terminus and that disruption of these domains can occur with only subtle effects on receptor binding. Identification of this mutation made it possible to identify the mutant allele within the family and to ascertain antenatally that it was not present in a 46,XY fetal sibling of the proband at 9 wk gestation.